2017
DOI: 10.3389/fnmol.2017.00356
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Involvement in Neurodegenerative Diseases of the Motor System: Insights from Lysosomal Storage Diseases

Abstract: Lysosomal storage diseases (LSDs) are a heterogeneous group of rare inherited metabolic diseases that are frequently triggered by the accumulation of lipids inside organelles of the endosomal-autophagic-lysosomal system (EALS). There is now a growing realization that disrupted lysosomal homeostasis (i.e., lysosomal cacostasis) also contributes to more common neurodegenerative disorders such as Parkinson disease (PD). Lipid deposition within the EALS may also participate in the pathogenesis of some additional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 167 publications
(180 reference statements)
1
30
0
Order By: Relevance
“…Dysregulation of GlcCer and other glycosphingolipids (e.g., GM1a) was previously reported by us and others in ALS patients and in animal models (Dodge et al, 2015; Henriques et al, 2015; Dodge, 2017; Henriques et al, 2017; Henriques et al, 2018).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Dysregulation of GlcCer and other glycosphingolipids (e.g., GM1a) was previously reported by us and others in ALS patients and in animal models (Dodge et al, 2015; Henriques et al, 2015; Dodge, 2017; Henriques et al, 2017; Henriques et al, 2018).…”
Section: Discussionsupporting
confidence: 71%
“…Beyond their role in energy metabolism, lipids and particularly sphingolipids are modulators of cellular signaling pathways and participate in the maintenance and repair of the various components of the motor axis such as neurons and muscles. Our transcriptomic studies on muscle biopsies in ALS patients showed a significant increase in the expression of the UGCG gene (UDP-glucose ceramide glucosyltransferase), encoding the sphingolipid metabolism enzyme that synthesizes glucosylceramide (GlcCer) (Henriques et al, 2015; Dodge, 2017; Henriques et al, 2017). It has been shown in ALS that GlcCer and ceramide levels are deregulated (Cutler et al, 2002; Dodge et al, 2015; Henriques et al, 2015; Henriques et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…Elevated diacylglycerols have been reported in the frontal cortex of patients diagnosed with Alzheimer's disease (Wood et al, 2016 ) and levels of sphingolipids, phospholipids, and neutral lipids were reported as significantly dysregulated in the central nervous system (CNS) of patients diagnosed with Parkinson's disease (Cheng et al, 2011 ). Genetic mutations causing disrupted lipid metabolism have been linked to neurological and neuromuscular phenotypes in human diseases, like hereditary spastic paraplegia (Dodge, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lipids perform the regulatory role by acting as secondary messengers in the inflammation processes during ALS development which are accompanied by the activation of microglia, loss of neuromuscular junctions, and subsequent degeneration of motor neurons. At the same time, the level of neurotoxic molecules synthesized with an active involvement of lipid messengers increases (93).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%